2021
DOI: 10.5194/acp-21-12479-2021
|View full text |Cite
|
Sign up to set email alerts
|

Variability in black carbon mass concentration in surface snow at Svalbard

Abstract: Abstract. Black carbon (BC) is a significant forcing agent in the Arctic, but substantial uncertainty remains to quantify its climate effects due to the complexity of the different mechanisms involved, in particular related to processes in the snowpack after deposition. In this study, we provide detailed and unique information on the evolution and variability in BC content in the upper surface snow layer during the spring period in Svalbard (Ny-Ålesund). A total of two different snow-sampling strategies were a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Berto et al. (2021) showed that the impacts of BC, which come from long‐distance BB episodes, might be overestimated. The climate in the high Arctic is changing at twice the rate of the rest of the world (Walsh, 2014; Yu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berto et al. (2021) showed that the impacts of BC, which come from long‐distance BB episodes, might be overestimated. The climate in the high Arctic is changing at twice the rate of the rest of the world (Walsh, 2014; Yu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that mid/high latitude boreal forest fires in summer contribute significantly to the aerosol burden over the Arctic (Jacob et al, 2010;Raut et al, 2017). Several studies have also addressed the BC concentration over the Arctic (Berto et al, 2021;Zdanowicz et al, 2021). Berto et al (2021 showed that the impacts of BC, which come from long-distance BB episodes, might be overestimated.…”
mentioning
confidence: 99%